Volcanic Origin of a Long‐Lived Swarm in the Central Bransfield Basin, Antarctica. Issue 1 (29th December 2021) - Poli, P.; Cabrera, L.; Flores, M. C.; Báez, J. C.; Ammirati, J. B.; Vásquez, J.; Ruiz, S.
Abstract: Understanding the extensional processes in tectonic context at the transition from continental to oceanic spreading is fundamental to obtain new insights about formations of new oceans. To that scope, we study a large and long‐lived earthquake swarm occurring in 2020–2021 in a back‐arc rift (the Bransfield Basin) south of the South Shetland Islands, Antarctica. We make use of one local seismological station to detect more than 36, 000 small earthquakes, occurring from August 2020 to June 2021. Together with the occurrence of earthquakes, we observe a significant, geodetic deformation at a nearby GPS station. By joint interpretation of b‐value, spatiotemporal evolution of seismicity and geodetic deformation, we infer a volcanic origin for this swarm that takes place close to the ridge axis. Our study suggests that beyond the 7 mm/yr deformation reported at the Bransfield Basin ridge, transient deformation episodes localized at the ridge axial volcanic structure also modulate the extension. Plain Language Summary: Understanding the extensional tectonics in places at the transition from continental to oceanic spreading, can provide new insights about the extensional processes leading to formation of new oceans. We report on a long‐lived (∼1 year) earthquake swarm in the Bransfield Basin, just south of the South Shetland islands, in Antarctica, that brings new observations to such tectonics. This basin represents a ridge separating two tectonic plates and is characterized by extensional tectonics at the transition from back‐arc rifting to ocean spreading. By detection and characterization of more than 36, 000 earthquakes and observation of associated geodetic deformation, we inferred the significant role played by volcanic processes occurring at the ridge axis, in modulating extension of the basin. This observation differs from models of purely tectonic extensional processes involving rift bounding border faults. Key Points: We characterized one of the largest swarms ever recorded in a spreading ridge Analysis of seismological and geodetic data suggest volcanic origin for this swarm We infer a significant role played by axial volcanic structures in opening of spreading ridges